Children's Perception of the Parenting in Supporting Learning Activities - Mega Selvia; Daharnis Daharnis (Universitas Negeri Padang, 2019)
Learning activities are carried out by students in achieving learning goals. One factor that can support children's learning activities is parental treatment, among others in the form of, (1) meet the child's basic needs, (2) guiding children, (3) educating children. This research uses quantitative descriptive methods. The subjects in the study were elementary students in class IV, V, and VI consist of 75 people. Data collection tools used in the form of instruments (questionnaire) and data analysis using descriptive methods. Based on the research findings, children's perceptions of parental treatment in supporting learning activities classified as good, which includes: meeting basic needs, guiding, and educating children.